Representasi Pesan-Pesan Dakwah Humanis Dalam Novel “As Long The Lemon Trees Grow” Karya Zoulfa Katouh - Salsabilla Nabilla Anastasya; Mansur Hidayat; Abdul Syukur (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
Humanistic da’wah is an orientation of Islamic preaching that positions human beings as dignified subjects by strengthening empathy, compassion, justice, social care, and protection for vulnerable groups. Amid the rise of violence, intolerance, and humanitarian crises, literature can function as a medium of da’wah humanistic that does not preach didactically but touches readers’ affective experiences. This study aims to analyze the representation of humanistic da’wah messages in Zoulfa Katouh’s novel As Long as the Lemon Trees Grow. This research employs a qualitative approach with content analysis. The data consist of narratives, dialogues, character conflicts, and story symbols containing humanistic da’wah messages. The analysis applies Stuart Hall’s representation theory through three stages: identifying textual signs, categorizing humanistic da’wah values, and interpreting socio-religious meanings. The findings reveal six main categories: empathy toward war victims, sacrifice for the safety of others, social care in medical crises, moral responsibility, courage to protect vulnerable groups, and humanitarian solidarity. The novel demonstrates that humanistic da’wah is not always delivered through explicit sermons but can be articulated through ethical actions that preserve life and human dignity.